1993
DOI: 10.1111/j.1365-2672.1993.tb05151.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the selection and use of tetrazolium salts as cytochemical indicators of microbial viability and activity

Abstract: The reduction of four tetrazolium cations (TCs), nitroblue tetrazolium (NBT), neotetrazolium (NT), methylthiazolyldiphenyltetrazolium (MTT) and iodonitrophenyltetrazolium (INT), by viable micro-organisms, immobilized on glass cover slips, was examined by light microscopy with a view to determining a systematic basis for applying these reagents as cytochemical indicators of microbial viability and activity. The potential value of histochemical information about TC reactions for developing their microbiological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0
4

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(70 citation statements)
references
References 32 publications
2
64
0
4
Order By: Relevance
“…In a recent review, Ullrich et al (1996) describe a growing body of evidence which suggests that CTC is unsuitable for the enumeration of bacteria in environmental samples. The possible expla-nations for obtaining lower counts by CTC than by other direct methods of enumeration were (i) not all bacteria are capable of reducing tetrazolium salts (Thom et al 1993), (ii) the assay is not sensitive enough to detect bacteria with low rates of metabolic activity (Gasol et al 1995) and (iii) although CTC has been assumed to be non-toxic to bacteria (Rodriguez et al 1992), it has been reported that bacterial metabolic activity can be directly suppressed/inhibited by CTC, causing an under-estimation of the total number of bacteria within a sample (Ullrich et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent review, Ullrich et al (1996) describe a growing body of evidence which suggests that CTC is unsuitable for the enumeration of bacteria in environmental samples. The possible expla-nations for obtaining lower counts by CTC than by other direct methods of enumeration were (i) not all bacteria are capable of reducing tetrazolium salts (Thom et al 1993), (ii) the assay is not sensitive enough to detect bacteria with low rates of metabolic activity (Gasol et al 1995) and (iii) although CTC has been assumed to be non-toxic to bacteria (Rodriguez et al 1992), it has been reported that bacterial metabolic activity can be directly suppressed/inhibited by CTC, causing an under-estimation of the total number of bacteria within a sample (Ullrich et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that CTC may be toxic to some bacteria (Kaprelyants and Kell, 1993a;Ullrich et al, 1996) at the concentrations used, and might not work in some circumstances (Thom et al, 1993), but has been satisfactorily used to stain active bacteria from cultures (Kaprelyants and Kell, 1993a;López-Amorós et al, 1995aMcFeters et al, 1995), freshwater plankton (del Giorgio et al, 1997b;Yamaguchi and Nasu, 1997) and marine plankton (López-Amorós et al, 1998;Sieracki et al, 1999). A double staining protocol with SYTO 13 and CTC has been devised but requires a flow cytometer with double laser capabilities (López-Amorós et al, 1998).…”
Section: Single-cell Activitymentioning
confidence: 99%
“…Thom et al 1993), whereas others have suggested temperature (Tabor & Neihof 1984, Robarts & Sephton 1988, Sommaruga & Conde 1997, lysis (Proctor & Fuhrman 1990), grazing (Gasol et al 1995) and resource availability (del Giorgio & Scarborough 1995, Choi et al 1999. In terms of resource availability, a wide variety of sources including phytoplankton excretion and lysis (Cole et al 1988, Maurin et al 1997) and grazing and release by zooplankton (e.g.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%